Evaluation of a Reduced Graphene Oxide Antimony Nanocomposite Horseradish Peroxidase Biosensor Matrix for Hydrogen Peroxide. (2017) - Silwana, Bongiwe; van der Horst, Charlton; Iwuoha, Emmanuel; Somerset, Vernon
Abstract: An exploration of reduced graphene oxide impregnated with antimony nanoparticles to form a nanocomposite as a platform for the immobilization of horseradish peroxidase for the amperometric detection of hydrogen peroxide is presented. Electrochemical measurements revealed that the heterogeneous electron transfer constant (ks) was evaluated to be 0.37 s −1 . The average surface concentration of electro-active HRP on the surface of the modified glassy carbon electrode was calculated to be 9.43 × 10 −9 mol cm −2 . The voltammetric results revealed that the peak current of the modified electrode increased linearly with increasing concentration of hydrogen peroxide (from 1 nM to 4 nM) with a detection limit of 2.88 nM.